UPAYA TRANSPLANTASI TERUMBU KARANG (Acropora sp.) SEBAGAI REHABILITASI FUNGSI KAWASAN EKOSISTEM TERUMBU KARANG TERDAMPAK TUMPAHAN MINYAK ASPAL DI DESA AFULU KABUPATEN NIAS UTARA - Vindy Rilani Manurung; Ipanna Enggar Susetya; Hasbi Husaini; Hafizah Arinah; Wilman Nazara (Jurnal Abdi Insani, 2023)
A tanker that was transporting 1,900 tons of raw asphalt into the North Nias Marine Protected Area spilled it, contaminating the ocean up to 50 kilometers away from the North Nias Regency Marine Protected Area. Long-term effects on the coral reef ecosystem are anticipated to build up and result in a decline in fish catches. The community service team works to restore coral reef ecosystem areas utilizing coral reef transplanting technology as a solution to the partners problems. In accordance with the goals of the policy direction of the Sustainable Development Goals (SDGs) number 14 to increase conservation, rehabilitation, and disaster resilience in coastal and marine areas, to establish and develop a group of productive communities through KUB Harapan Wunga Nias Utara. Implementation of activities to solve KUB Harapan Wunga partner problems in Afulu Village, using counseling and simulation approaches carried out holistically. All activities go through four stages, preparation of activities, outreach, delivery of operational tools and materials, field activities simulating the search for coral donors and removing tables coral transplant shelf. The results of the activity were created and delivery of 15 units of transplant racks along with tools and materials which were handed over to community service partners, outreach and field activities attended by the Afulu Village Secretary, head of the Harapan Wunga Kelompok Usaha Bersama (KUB), 10 fishermen and 17 community service team students. The transplant shelf that has been removed at the location will be observed for every 2 weeks by the community service partner. This community service activity has a positive impact and a new understanding for the partners of the Harapan Wunga Kelompok Usaha Bersama (KUB) Afulu Village, Afulu District, North Nias Regency regarding the major influence of the function coral reef ecosystems for the catch of fishermen as well as providing new experience in the application of science and technology (IPTEK) for transplantation coral reefs. The implementation of community service succesfully, partners were very enthusiastic about carrying out coral reef transplantation simulation activities, besides that the role of lecturers and students in applying knowledge about management of conservation area utilization and management of coral reefs as well.